2021
DOI: 10.3390/ma14216318
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Ionic Liquid with Nanoparticles

Abstract: This research aims to formulate a new lubricant containing oxide nanoparticles for enhancing anti-wear ability and reducing friction. Different concentrations of copper oxide (CuO) and zinc oxide (ZnO) nanoparticles were separately added to an ionic liquid, methyltrioctylammonium bis(trifluoromethylsulfonyl)imide [N1888] [NTf2], to formulate the tested lubricants. The tribological properties of the lubricants were tested by performing ball-on-disc wear tests on a tribotester (MTM, PCS Instruments). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the recent development of lubricants, adding particles to lubricants is one of the important directions because they can enhance the lubricant's interfacial tribological properties. Among factors affecting the tribological performance of nanolubricants, the size and concentration of nanoparticles have been widely studied [1][2][3][4][5][6][7][8]. However, in the literature reports on particle additives, the optimal particle size or optimal concentration for different interface conditions varies greatly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent development of lubricants, adding particles to lubricants is one of the important directions because they can enhance the lubricant's interfacial tribological properties. Among factors affecting the tribological performance of nanolubricants, the size and concentration of nanoparticles have been widely studied [1][2][3][4][5][6][7][8]. However, in the literature reports on particle additives, the optimal particle size or optimal concentration for different interface conditions varies greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 0.3 wt% nanoparticles resulted in a good improvement in reducing friction, wear and scar formation on the surface. Ta et al [7] added different concentrations (0.2 and 0.5 wt%) of CuO and ZnO nanoparticles to the ionic liquid. This method could enhance the anti-wear ability and reduce friction of the ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third body mechanism, the ZnO NPs function as nano ball bearings, effectively transferring sliding friction into rolling friction and reducing the real contact pressure, resulting in low friction and wear. 47,54 Thus, the anti-wear mechanism of IL remains unchanged while the role of NPs switches from the most tribofilm formation to the most nano bearing effect in the hybrid nanolubricant R + IL + ZnO. Several studies have pointed out that ZnO NPs exhibited different wear mechanisms according to the base oil.…”
Section: Film Thicknessmentioning
confidence: 99%
“…51 A few studies have revealed that [N 1888 ] [NTf 2 ] could improve friction-reducing and wear-reducing properties when it serves as a neat lubricant 36,52 or additive in oils. 53 Ta et al 54 found that the IL formulated with ZnO NPs could enhance the tribological properties of IL when used as a neat lubricant in steel–steel contacts. However, interactions between [N 1888 ] [NTf 2 ] with other additives when used as hybrid nanolubricants in lubricating oils have not been studied.…”
Section: Introductionmentioning
confidence: 99%